2020
DOI: 10.3390/cells9092105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Serum Heat Shock Protein Levels as Novel Biomarkers for Atrial Fibrillation

Abstract: Background: Staging of atrial fibrillation (AF) is essential to understanding disease progression and the accompanied increase in therapy failure. Blood-based heat shock protein (HSP) levels may enable staging of AF and the identification of patients with higher risk for AF recurrence after treatment. Objective: This study evaluates the relationship between serum HSP levels, presence of AF, AF stage and AF recurrence following electrocardioversion (ECV) or pulmonary vein isolation (PVI). Methods: To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…Previous studies revealed an increase in HSPB1 levels 24 and HSPA1 levels 21 in follow-up serum samples of patients who developed AF recurrence post-ablative therapy. Such an increase in HSPs in follow-up serum samples was not observed in the current study, which may be due to presence of underlying heart diseases.…”
Section: Hsps As a Potential Marker To Stage Afmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies revealed an increase in HSPB1 levels 24 and HSPA1 levels 21 in follow-up serum samples of patients who developed AF recurrence post-ablative therapy. Such an increase in HSPs in follow-up serum samples was not observed in the current study, which may be due to presence of underlying heart diseases.…”
Section: Hsps As a Potential Marker To Stage Afmentioning
confidence: 93%
“…However, Cao, et al 23 described that patients undergoing mitral valve replacement with AF revealed higher plasma HSPD1 levels compared to patients in sinus rhythm. No previous studies, except for our recent study 24 , investigated serum HSPB7 as a marker to stage AF.…”
Section: Hsps As a Potential Marker To Stage Afmentioning
confidence: 99%
“…This trial investigated whether HSP levels in serum discriminate between control and the various stages of AF and predict AF recurrence after treatment. Importantly, serum HSPA1, HSPB1, HSPB7, and HSPD1 levels did not discriminate between the presence or stage of AF, nor did it identify patients at risk of AF recurrence after electrical cardioversion or pulmonary vein ablation [ 17 ]. However, follow-up serum HSPB1 levels predict AF recurrence in patients undergoing ablative therapy.…”
Section: Hsps As Biomarkers In Afmentioning
confidence: 99%
“…However, follow-up serum HSPB1 levels predict AF recurrence in patients undergoing ablative therapy. Here, serum HSPB1 levels significantly increased at 3, 6, and 12 months post-ablation compared with patients without AF recurrence within 1 year post-ablation [ 17 ]. These results suggest that HSPB1 levels may be useful in predicting recurrence of AF after ablative therapy.…”
Section: Hsps As Biomarkers In Afmentioning
confidence: 99%
See 1 more Smart Citation